2021
DOI: 10.34766/fetr.v47i3.917
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected suicide risk factors and the level of spirituals transcendence and religiosity

Abstract: Suicide is a global phenomenon and one of the leading causes of death worldwide. The analysis covers suicidal risk factors (depression, psychological pain, fascination with death) and protective factors (spirituality, religiosity) in the population of healthy people in the SARS-CoV-2 pandemic and the relationship between recent stressful events and suicide risk factors. In the period from October 2020 to March 2021, 260 people aged 18-63 were surveyed electronically, using the own questionnaire and Polish adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 25 publications
3
7
1
Order By: Relevance
“…A study from the SARS-CoV-2 pandemic period of 2020-2021 showed that 38.8% of "healthy Poles" show symptoms of depression and require consultation with a specialist. This study also showed that among "healthy Poles", depression positively correlates with religious crisis, fascination with death, life stressors, and psychological pain (Surmacz et al, 2021). It was also shown that with greater severity of depressive symptoms, there is a higher level of professional burnout (Kornakiewicz et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…A study from the SARS-CoV-2 pandemic period of 2020-2021 showed that 38.8% of "healthy Poles" show symptoms of depression and require consultation with a specialist. This study also showed that among "healthy Poles", depression positively correlates with religious crisis, fascination with death, life stressors, and psychological pain (Surmacz et al, 2021). It was also shown that with greater severity of depressive symptoms, there is a higher level of professional burnout (Kornakiewicz et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
“…In the same year: the global suicide rate was 10.5; the European rate was 12.9; the Polish rate was 13.4. In Poland, this rate for women was 3.4; for men 23.9 (Surmacz et al, 2021). Studies show that men commit suicide about 1.8-3 times more often than women.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The importance of resilience in reducing the severity of psychiatric symptoms once they have occurred is described. The results of research relating to the correlation between spirituality and experi-encing mental health disruptions are inconclusive although this issue is often addressed in relation to the analysis of health care issues (Puchalski, 2001;Puchalski, 2004;Godlewska et al, 2018;Surmacz et al, 2021). Most of the available literature emphasises the importance of high levels of religiosity in the prevention of the occurrence of mental disorders and, in addition, a significant factor influencing an individual's overall well-being (Gruszynski, 2016;Abdolkarimi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%